Numerical Analysis on Shear Behavior of Joints under Low Confining and Eccentric Loads. (30th April 2019) - Chen, Gongfa; Fang, Zhuangcheng; Wang, Shaodi; Jiang, Haibo; Liang, Hualian
Abstract : The joints of precast concrete segmental beams (PCSBs), which are in complex stress status and susceptible to failure, are very important parts of the structure. In this paper, a finite element model was established to study the shear performance of single-keyed joints. The plastic damage model was used to simulate the cracking of specimens. Three types of single-keyed joints were investigated, including the dry joint with normal concrete (NC), dry joint with steel fiber-reinforced concrete (SFRC), and epoxied joint with NC. The cracking pattern, ultimate shear strength, and load-displacement curve for these specimens were obtained. Based on these numerical simulation models, extended analyses in terms of low confining pressures and eccentric loads were performed. It has been found that the influence of fiber-reinforced concrete should be considered. The ultimate shear strength of specimens reduced with the reduction of confining pressure. When an eccentric load was applied, a lower shear capacity would be obtained. Under the low confining stress, the AASHTO LRFD 2014 provision underestimated the shear strength of single-keyed dry joints with both NC and SFRC, while the shear capacity of single-keyed dry joints with both NC and SFRC has been overestimated under the eccentric loads.